MEMORY FAILURES IN DAILY LIFE AMONG MIDDLE AGED WOMEN WITH AND WITHOUT BREAST CANCER HISTORY. (11th November 2018) - Scott, S B; Mogle, J; Small, B J; Sliwinski, M J
Abstract: "Chemo-brain" (post-chemotherapy cognitive impairment) is a concern among cancer survivors. The memory lapses (i.e., keys, names, reason for entering room) survivors experience may function as stressors and increase negative mood. We compared breast cancer survivors (N=47, Mage=53.0) and an age-matched sample of women without cancer history (N=91, Mage=51.8) on their exposure to memory lapses and related changes in negative affect (NA) for 14 days. Results indicated that survivors were significantly more likely to report a memory lapse (OR=1.70, p=.01, CI 1.15–2.51). NA was higher on days with memory lapses (b=1.91, SE=.34, p<.01). Survivors, however, reported lower NA on days without memory lapses (b=-7.47, SE=2.92, p=.01) and their NA increased less on days with memory lapses (bsurvivor=.97, SE=.56; bnon=2.85, SE=.40, p=.01) than women without cancer history. In sum, survivors may be at risk for more frequent lapses but may be less negatively emotionally impacted by them.